2021
DOI: 10.1029/2020gl092200
|View full text |Cite
|
Sign up to set email alerts
|

Regional Drought Risk in the Contiguous United States

Abstract: In this study, we provide an outlook for regional drought risk in the contiguous US (CONUS) in the near future based on ongoing drought trends, and assess its impacts on soil moisture, streamflow, and water supply in different regions. It is found that the meteorological drought risk has been decreasing in northern parts of the CONUS and increasing in the Southwest and Southeast United States (US). In the Southwest US, droughts are associated with severe deficits in soil moisture and streamflow, which can adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 88 publications
0
12
0
2
Order By: Relevance
“…Previous studies have attempted to capture the change in drought parameters during the drought propagation process by comparing the cumulative distribution functions of different types of droughts [15,16,19,20]. Apurv et al [15] suggested that the drought propagation process can be quantified by a ratio such as the drought propagation ratio, as shown in Equation (7) and Equation ( 8 However, the drought propagation ratios above can only capture the difference in the distribution of drought parameters, while the difference in the frequency of drought events is not considered.…”
Section: Drought Propagationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have attempted to capture the change in drought parameters during the drought propagation process by comparing the cumulative distribution functions of different types of droughts [15,16,19,20]. Apurv et al [15] suggested that the drought propagation process can be quantified by a ratio such as the drought propagation ratio, as shown in Equation (7) and Equation ( 8 However, the drought propagation ratios above can only capture the difference in the distribution of drought parameters, while the difference in the frequency of drought events is not considered.…”
Section: Drought Propagationmentioning
confidence: 99%
“…𝑇 𝑗 is the corresponding return period, t is the total time length of the study period (67 years), 𝑛 𝑠 and 𝑛 𝑚 are the numbers of soil moisture droughts and meteorological droughts, respectively. Drought propagation ratios are regarded as constant features of basins in previous studies and are determined by climate features and underlying properties [20]. Since the regional climate and underlying surface might change during the study period, the propagation ratios are also calculated by a moving-window method (see Section 3.5 for details).…”
Section: Drought Propagationmentioning
confidence: 99%
See 2 more Smart Citations
“…The changing climate may not influence the snowpack accumulation, melt and subsequent runoff uniformly [12]. Since these drier conditions are leading to a more uncertain future [13,14], an understanding of the spatial distribution of the snowpack is vital for management of water resources [15]. Spatial patterns of snow distribution have been considered at various scales [16] from local [17] to regional [18].…”
Section: Introductionmentioning
confidence: 99%